Advances and current challenges in calcium signaling - Kudla, Jörg; Becker, Dirk; Grill, Erwin; Hedrich, Rainer Franz; Hippler, Michael; Kummer, Ursula; Parniske, Martin; Romeis, Tina; Schumacher, Karin (The new phytologist, 2018)
Content Summary 414 I. Introduction 415 II. Ca2+ importer and exporter in plants 415 III. The Ca2+ decoding toolkit in plants 415 IV. Mechanisms of Ca2+ signal decoding 417 V. Immediate Ca2+ signaling in the regulation of ion transport 418 VI. Ca2+ signal integration into long-term ABA responses 419 VII Integration of Ca2+ and hormone signaling through dynamic complex modulation of the CCaMK/CYCLOPS complex 420 VIII Ca2+ signaling in mitochondria and chloroplasts 422 IX A view beyond recent advances in Ca2+ imaging 423 X Modeling approaches in Ca2+ signaling 424 XI Conclusions: Ca2+ signaling a still young blooming field of plant research 424 Acknowledgements 425 ORCID 425 References 425 Summary Temporally and spatially defined changes in Ca2+ concentration in distinct compartments of cells represent a universal information code in plants. Recently, it has become evident that Ca2+ signals not only govern intracellular regulation but also appear to contribute to long distance or even organismic signal propagation and physiological response regulation. Ca2+ signals are shaped by an intimate interplay of channels and transporters, and during past years important contributing individual components have been identified and characterized. Ca2+ signals are translated by an elaborate toolkit of Ca2+-binding proteins, many of which function as Ca2+ sensors, into defined downstream responses. Intriguing progress has been achieved in identifying specific modules that interconnect Ca2+ decoding proteins and protein kinases with downstream target effectors, and in characterizing molecular details of these processes. In this review, we reflect on recent major advances in our understanding of Ca2+ signaling and cover emerging concepts and existing open questions that should be informative also for scientists that are currently entering this field of ever-increasing breath and impact.